Bp-13 PLA2: Purification and Neuromuscular Activity of a New Asp49 Toxin Isolated from Bothrops pauloensis Snake Venom - Georgina Sucasaca-Monzón; Priscila Randazzo-Moura; Thalita Rocha; Frank Denis Torres-Huaco; Augusto Vilca-Quispe; Luis Alberto Ponce-Soto; Sérgio Marangoni; Maria Alice da Cruz-Höfling; Léa Rodrigues-Simioni (Biochemistry Research International)
A new PLA2 (Bp-13) was purified from Bothrops pauloensis snake venom after a single chromatographic step of RP-HPLC on μ-Bondapak C-18. Amino acid analysis showed a high content of hydrophobic and basic amino acids and 14 half-cysteine residues. The N-terminal sequence showed a high degree of homology with basic Asp49 PLA2 myotoxins from other Bothrops venoms. Bp-13 showed allosteric enzymatic behavior and maximal activity at pH 8.1, 36°–45°C. Full Bp-13 PLA2 activity required Ca2+; its PLA2 activity was inhibited by Mg2+, Mn2+, Sr2+, and Cd2+ in the presence and absence of 1 mM Ca2+. In the mouse phrenic nerve-diaphragm (PND) preparation, the time for 50% paralysis was concentration-dependent (P<0.05). Both the replacement of Ca2+ by Sr2+ and temperature lowering (24°C) inhibited the Bp-13 PLA2-induced twitch-tension blockade. Bp-13 PLA2 inhibited the contractile response to direct electrical stimulation in curarized mouse PND preparation corroborating its contracture effect. In biventer cervicis preparations, Bp-13 induced irreversible twitch-tension blockade and the KCl evoked contracture was partially, but significantly, inhibited (P>0.05). The main effect of this new Asp49 PLA2 of Bothrops pauloensis venom is on muscle fiber sarcolemma, with avian preparation being less responsive than rodent preparation. The study enhances biochemical and pharmacological characterization of B. pauloensis venom.